1978
DOI: 10.1021/i360066a016
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Kuwait Crudes. 1. Composition Analysis of Some Asphalts and Their Sulfurized Products

Abstract: The differences in the chemical composition of five asphalts and one air-blown bitumen, obtained from Kuwait crudes, were studied using the densimetric technique. Two asphalts were then reacted with different weight percent of sulfur at 220 °C, and the effect of sulfur was followed by studying the composition analysis of the products. The results obtained revealed that the reaction with sulfur leads to an increase in the percent of asphaltene, which contains most of the bonded sulfur. It was also found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The conditions of reaction were chosen from the previous works reported in the literature (Petrossi et al, 1972;Al-Farkh et al, 1978;Obiaga et al, 1982). Petrossi et al (1972) have shown that sulphur at its melting point (about 140 • C) enters into chemical linkages with asphalt hydrocarbons forming polar compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The conditions of reaction were chosen from the previous works reported in the literature (Petrossi et al, 1972;Al-Farkh et al, 1978;Obiaga et al, 1982). Petrossi et al (1972) have shown that sulphur at its melting point (about 140 • C) enters into chemical linkages with asphalt hydrocarbons forming polar compounds.…”
Section: Methodsmentioning
confidence: 99%